Sentiment analysis of emotionally expressive ethnicity assessment (based on the internet posts) - Hirnyak Oleg (онлайн, 2022)
Sentiment analysis is a computational branch of research into people's thoughts, moods,emotions, and attitudes. This fascinating problem is becoming increasingly important in society. The emergence and rapid development of sentiment analysis is associated with the popu arity of social media, discussions on forums, blogs, etc. Considering that this data is full of diverse judgments, moods, and ideas about the world, user content has become the subject of research by a wide range of scientists. There is a need for automatic sentiment analysis, whereas the amount of data is extremely large. Sentiment analysis offers many complex research tasks. It also includes useful information for anyone interested in sentiment analysis and social media analysis. The widespread use of social networks and their role in modern society is one of the most interesting innovations in recent years. The close links that often arise between users create a space for discussions that motivate, engage, and unite people with common goals and encourage various forms of collective actions. Data from the web allows us to understand and explain many complex social phenomena and anticipate them. Only in the case that data is correctly collected and analysed. In this context, sentiment analysis tries to make clear what people think. Furthermore, it provides ideas, models, and algorithms that can turn unstructured text into informative data.